2015
DOI: 10.1016/j.neulet.2015.02.029
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome regulates transcription-favoring histone methylation, acetylation and ubiquitination in long-term synaptic plasticity

Abstract: Histone modifications, such as lysine methylation, acetylation and ubiquitination, are epigenetic tags that shape the chromatin landscape and regulate transcription required for synaptic plasticity and memory. Here we show that transcription-promoting histone H3 trimethylated at lysine 4 (H3K4me3), histone H3 acetylated at lysine 9 and 14 (H3K9/14ac), and histone H2B monoubiquitinated at lysine 120 (H2BK120ub) are enhanced after the induction of long-lasting chemically-induced long-term potentiation (cLTP) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Recent evidence demonstrates that the proteasome may be involved in regulating gene activity during LTP, as proteasomal inhibition prevents transcription-promoting histone marks from occurring (Bach et al, 2015). Finally, some evidence suggests that DNA methylation is also regulated by the proteasome through regulated degradation of DNA methyltransferase enzymes (Esteve et al, 2009), thus positioning the proteasome as a regulator of crucial epigenetic processes.…”
Section: Protein Degradation In Memorymentioning
confidence: 99%
“…Recent evidence demonstrates that the proteasome may be involved in regulating gene activity during LTP, as proteasomal inhibition prevents transcription-promoting histone marks from occurring (Bach et al, 2015). Finally, some evidence suggests that DNA methylation is also regulated by the proteasome through regulated degradation of DNA methyltransferase enzymes (Esteve et al, 2009), thus positioning the proteasome as a regulator of crucial epigenetic processes.…”
Section: Protein Degradation In Memorymentioning
confidence: 99%
“…In contrast to the effect of Hp on gene transcription, the consequences of H methylation (Hme) depend on the number and location of the relevant methyl groups (Bach et al, 2015). A growing number of studies have revealed that Hme is involved in memory formation.…”
Section: Introductionmentioning
confidence: 99%
“…This investigation showed that H2BK120ub levels oscillate after the induction of cLTP: an increase in histone H2B monoubiquitination was observed immediately after cLTP induction and at 30 min after cLTP induction, but not at 15 min (Bach et al, 2015). This finding is consistent with previous studies of histone H2B monoubiquitination in yeast transcriptional regulation, where multiple rounds of histone ubiquitination and deubiquitination are required for transcription initiation and elongation, respectively (Minsky et al, 2008; Weake and Workman, 2008; Wyce et al, 2007).…”
Section: The Upp and Long-term Synaptic Plasticitymentioning
confidence: 97%
“…For example, a novel role of the proteasome in modulation of epigenetic histone modifications was described. This study demonstrated that trimethylation of histone 3 at lysine 4 (H3K4me3), acetylation of histone H3 at lysines 9 and 14 (H3K9/14ac), and monoubiquitination of histone H2B at lysine 120 (H2BK120ub) are enhanced immediately after cLTP induction and their enhancement is blocked by β-lactone pretreatment (Bach et al, 2015). …”
Section: The Upp and Long-term Synaptic Plasticitymentioning
confidence: 99%
See 1 more Smart Citation